THE TEMPERATURE DEPENDENCE OF STABILITY CONSTANTS FOR THE FORMATION OF POLYNUCLEAR CATIONIC COMPLEXES - Plyasunov A.V.; Grenthe I. (My University, 1994)
The temperature dependence of the formation of polynuclear cationic complexes is analyzed on the basis of a simple electrostatic model of electrolytic dissociation proposed by Ryzhenko and Bryzgalin . It is possible to expand this theory to the case of polynuclear cationic complexes, considering the formation of such complexes as a result of two competing processes: a nonelectrostatic attraction and an electrostatic repulsion of the spheres consisting of mononuclear “building blocks.” The relative stability of polynuclear complexes decreases with temperature because of the large increase of electrostatic repulsion due to the decrease of the dielectric constant of water. The predictive properties of the model is exemplified by the system Al+3-OH−, where it is possible to describe the temperature dependence of stability constants for both mononuclear and polynuclear complexes up to 200–250°C at saturation water vapor pressure using the values of logKo(298, 1) and only one fitting parameter a, which has the same value for all complexes in the system Al+3-OH−(a is close to the metal-hydroxide/oxide bond distance). Additional experimental data for the formation of polynuclear hydroxide complexes of divalent Mg, Co, Ni, Pb, and UO22+ confirmed the predictive properties of the model. The proposed model may be used to estimate entropies of hydrolysis reactions. These turn out to follow the empirical correlations previously established by Baes and Mesmer (1976) very well.